GRAVITY FIELD: THEORETICAL AND EXPERIMENTAL CONTRIBUTION TO STUDY WEIGHING PENDULUM PERIOD - Nguimbous-Kouoh, Jean Jacques; Bum, Elisabeth Ngo; Ngos, Simon (JOURNAL OF ADVANCES IN PHYSICS, 2015)
We present in this article a theoretical study and experimental variations of the period of a pendulum consisting of a heavy rigid rod on which we can translate a mass . The study was conducted at the National Advanced School of Engineering, University of Yaounde I. The product was manufactured in a metal carpenter room for a relatively modest cost. The study is carried out in dependence on the position of the mass relative to the axis of rotation. We show that the model developed in the context of solid mechanics fits successfully experience while one developed in the context of the approximation of the mechanical point has only limited validity range, the asymptotic behavior for which the mass is from the axis of rotation. We define explicitly the field and compare with experiment.